Manual Reduction of Incarcerated Inguinal Hernia in Children - Thapa, Bijay; Pun, Madhusudan (Journal of Nepal Paediatric Society, 2013)
Introduction: Incarceration of an indirect inguinal hernia in children is an acute emergency and one of the common complications that may occur before herniotomy. Inguinal hernias rarely go away, and therefore, virtually all should be repaired at any age of presentation. Incarcerated inguinal hernia can be reduced successfully by manual reduction if performed by experienced hands on time. The objective of this study was to assess the safety and efficacy of manual reduction of incarcerated indirect inguinal hernia. Materials and Methods: Thirty six patients who attended Emergency Department of Kanti Children’s Hospital over 30 months period from January 2009 to July 2011 were studied prospectively. All patients were diagnosed case of inguinal hernia and waiting for elective herniotomy. Results: There were 30(83.33%) males and 6(16.66%) females, with male-to-female ratio of 5:1. Right sided inguinal hernia was 20(55.5%) and left 16(44.44%). The ages ranged from 1.5 months to 28 months with mean age of 15 months. Time of incarceration ranged from 3 hours to 30 hours. Manual reduction was successful in 30(83.33%). Remaining six had to undergo emergency surgery. Four patients with edematous but viable hernial contents had successful surgical reduction. Two patients with gangrenous small bowel loops had bowel resection and anastomosis. Conclusion: Manual reduction is safe and effective when performed timely. Herniotomy should be done without delay once diagnosed to avoid unnecessary complications. DOI: http://dx.doi.org/10.3126/jnps.v32i3.6146 J. Nepal Paediatr. SocVol.32(3) 2012 229-232